Renderings of paronymous infinitive constructions in OG Exodus and implications for defining the character of the translation - Perkins, Larry J. (HTS teologiese studies, 2022)
This article gives insight into the world of 3rd century BCE Alexandrian Judaism by analysing one aspect of the Greek translation of Exodus and provides a detailed evaluation of the way the translator managed to express the essence of the Hebrew text of Exodus while reflecting to some degree the form of the Hebrew text. No previous study only analyses this translator’s treatment of Hebrew paronymous infinitive absolute constructions in Greek Exodus. This research contributes to the preparation of a commentary on Greek Exodus in the Society of Biblical Literature Septuagint Commentary Series. Using the Göttingen text of Greek Exodus prepared by John William Wevers, it evaluates how this translator rendered each occurrence of a paronymous infinitive absolute construction in Hebrew Exodus, defining the primary modes employed and also seeking to explain variations from these norms. The primary method incorporates a close exegetical reading of both the Hebrew and Greek texts and comparing their texts, in order to discern how the translator treated this Hebrew idiom and illustrating his translation approach.Contribution: The results contribute to our understanding of how the translator of Greek Exodus approached his task. He was more concerned to express the sense of the Hebrew text, than producing a literal translation. He generally follows the Hebrew text’s word order, but is creative in his choice of Greek equivalents, often showing sensitivity to context and Greek idiom. This translation approach differentiates this translator’s approach somewhat from those responsible for other portions of the Pentateuch.